Effect of Energy Density on the Physical Properties of Resin-Based Restorative Materials when Polymerized with Quartz-Tungsten Halogen or LED-Light - Ruttermann, Stefan; Tomruk, Senay; Raab, Wolfgang H. M.; Janda, Ralf (European Journal of Dentistry, 2010)
Objectives: The purpose of this study was to evaluate flexural strengths, moduli, and maximum deflection of Clearfil AP-X (APX) and Ceram-X Mono (CXM) when cured with a quartz-tungsten halogen (QTH) or an LED-light (LED).Methods: Specimens were made according to ISO 4049 and cured with QTH or LED for 10, 20 or 60 s. Flexural strength, modulus, and deflection were determined after 24 h water storage at 37°C and after thermocycling. Statistical significance was P<.05.Results: Flexural strength did not depend on energy density or curing light and was significantly higher for APX than for CXM but decreased after thermocycling for both materials. Modulus and deflection depended on energy density. Modulus was significantly higher for APX than for CXM and increased for APX but decreased for CXM after thermocycling. Deflection decreased with increasing energy density and decreased after thermocycling. Though energy density did not influence flexural strength, it positively correlated with flexural modulus and negatively with maximum deflection.Conclusions: Energy density did not influence flexural strength but modulus and deflection. Thermocycling affected all material properties. The LED was as effective as the QTH. (Eur J Dent 2010;4:183-191)
Keywords: Resin-based filling material; Mechanical properties; LED; Curing device; Curing time